Not My Choice: The Lived Experiences of Freshman Pre-service Teachers Enrolled in a Non-Preferred Program in Central Luzon, Philippines - Pediongco, Jeramie Bermudez; Calaguas, Glenn Medallon (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: Teachers play a crucial role in national development, with their passion and commitment being essential to student success. However, one of the necessary elements to become passionate and committed to the teaching profession is to enroll first in an undergraduate teacher education program because this leads to better preparation. Thus, this study sought an in-depth look into the program commitment and academic experiences of first-year preservice teachers enrolled in a non-preferred program. Methodology: This phenomenological research explored the lived experiences of freshman pre-service teachers enrolled in a non-preferred program. The experiences of the nine informants were explored by conducting interviews focusing on realities that happen when enrolled in a non-preferred program. Particularly, conversational interviewing was used for an in-depth idea of thought processes and worldviews. Moreover, the Colaizzi’ method was followed. Main Findings: Findings revealed that the informants faced disappointments, educational challenges, later appreciation of the program, motivation from support systems, and aspirations for a better future. These ranges of experiences can be further categorized into five themes: (a) recognizing educational aspirations, (b) transitioning to higher education, (c) embracing the current program, (d) achieving personal growth, and (e) traversing to the future. Novelty/Originality of this study: This study offers an original contribution by closely examining how students in non-preferred academic programs develop academic commitment through adaptive processes over time. It highlights the importance of support systems, broad opportunities and positive academic experiences, and how these factors helps with students' internal coping strategies and identity reconstruction. The study reveals a nuanced, multi-phase progression—from initial disengagement to eventual integration—driven by institutional resources, peer interactions, and emerging self-agency. This progression addresses a gap in understanding how educational environments creates positive learning experiences and sustained commitment in misaligned academic placements.